Pushback: the political fallout of unpopular Supreme Court decisions - Bridge, Dave (Studies in constitutional democracy, 2024)
"Pushback explores the ways in which the minority party in Congress, and the minority political party more generally, can use unpopular decisions of the U.S. Supreme Court to drive a wedge into the majority party coalition"--